Question #a53f5
3 Answers
Explanation:
We have
We must get a common denominator. This is
See the answer below...
Explanation:
Z=(1+i)/(1-i)+2/(1+i)Z=1+i1−i+21+i
=>Z=((1+i)^2+2(1-i))/(1-i^2)" "["simple addition"]⇒Z=(1+i)2+2(1−i)1−i2 [simple addition]
=>Z=(1+2i+i^2+2-2i)/(1-i^2)⇒Z=1+2i+i2+2−2i1−i2
=>Z=(1+2i-1+2-2i)/(1+1)" "[i^2=-1]⇒Z=1+2i−1+2−2i1+1 [i2=−1]
=>Z=1⇒Z=1
=>color(red)(ul(bar(|color(green)(Z=1+0 cdot i)| Hope it helps...
Thank you..
Explanation:
You need to find a common denominator, add and simplify (understanding that